Atypical Lipomatous Tumor/Well-Differentiated Liposarcoma with Intramuscular Lipoma-Like Component of the Thigh. (14th December 2020) - Burusapat, Chairat; Wongprakob, Nuttadon; Wanichjaroen, Nutthapong; Pruksapong, Chatchai; Satayasoontorn, Kantang
Abstract : Atypical lipomatous tumor/well-differentiated liposarcoma (ALT/WDLPS) is a locally aggressive mesenchymal neoplasm composed either entirely or partly of an adipocytic proliferation showing at least focal nuclear atypia in both adipocytes and stromal cells. ALT most frequently occurs in deep soft tissue of proximal extremities (thigh and buttock) and usually presents as a deep-seated, painless mass that can slowly attain a very large size, which is one of the most common sarcomas of extremity. In the patients who presented with deep-seated tumor, distinction between intramuscular lipoma and well-differentiated liposarcoma is important due to the differences in treatment and prognosis. However, atypical well-differentiated liposarcoma with intramuscular lipoma-like component of the thigh is extremely rare. Moreover, the infiltrative growth pattern or intramuscular component may lead to a misinterpretation as intramuscular lipoma on a small biopsy. We present an unusual case of a female who presented with symptomatic mass at the thigh which has rarely been reported in English literature as an infiltrative intramuscular lipoma-like growth pattern of well-differentiated liposarcoma. Therefore, preoperative diagnosis is necessary, and correlation with imaging studies is required when one encounters with a large deep-seated mass. Atypical lipomatous tumor or well-differentiated liposarcoma should be kept in mind in the patient who presents with abnormal thigh mass.